Respuesta :

x^2 +12x =11

x^2 +12x -11 =0

x^2 +2*6x -11 =0 add to both sides 47

x^2 +12x +36 = 47

(x+6)^2 = 47

hope this will help you 

For this case we have a polynomial of the form:

[tex] x ^ 2 + 12x = 11
[/tex]

To complete the square, we must add on both sides of the equation a term of the form:

[tex] (\frac{b}{2}) ^ 2
[/tex]

Where,

b: coefficient of the exponent term equal to 1

We have then that for this case, completing squares:

[tex] x ^ 2 + 12x + (\frac{12}{2}) ^ 2 = 11 + (\frac{12}{2}) ^ 2
[/tex]

Rewriting we have:

[tex] x ^ 2 + 12x + (6) ^ 2 = 11 + (6) ^ 2

x ^ 2 + 12x + 36 = 11 + 36
[/tex]

Answer:

The number that should be added to both sides of the equation to complete the square is:

36